Heavy Mineral Survey of the Syrian Beach Sands, South of Tartous: Their Nature, Distribution and Potential - Bassam Kattaa (Canadian Institute of Mining, Metallurgy and Petroleum, 2002)
"Abstract - A heavy mineral survey of beach and dune sands including geochemical analysis for trace elements was undertaken to evaluate the economic potential of the sands and to understand the nature and distribution of the heavy minerals relative to potential source rocks. Results indicate that heavy minerals are generally derived from outcropping volcanic rocks that comprise a proportion of the hinterland in the south part of our survey area. The most abundant minerals are magnetite and pyroxene. The morphologies of the heavy mineral grains are angular to subangular, suggesting that they were transported short distances from the source rocks. Factors controlling heavy mineral distributions include wave and wind action, proximity to provenance, the fluvial drainage network, and longshore currrents.The most economically important mineral is ilmenite. Zircon and rutile concentrations are relatively minor and thus have lower economic potential."